Groundwater Prediction Analysis for Sustainable Development in Okeigbo, Southwestern Nigeria: A GIS supported AHP Approach - Olumuyiwa Olusola Falowo; Moses Philip Otuaga; Emmanuel Ajibola Lasore; Williams Kunle Olabisi; Gbenga Olaifa (Indonesian Journal of Earth Sciences, 2023)
Multi-criteria decision analysis with GIS-supported Analytical Hierarchy Process (AHP) has been undertaken in Okeigbo, Southwestern Nigeria to predict the hydrogeologic significance of the aquifers and in relation to the geologic units; quartzite, quartz schist, and metadiorite. Six parameters of higher hydrogeologic importance were pairwise and weighted respectively: AQT-aquifer layer thickness (0.07), AQR-aquifer layer resistivity (0.16), OVT-overburden thickness (0.10), TR-transverse resistance (0.20), TMY-transmissivity (0.26), CoA-coefficient of anisotropy (0.22). Subsequently, the GWPIV ranged from metadiorite 1.08 (weathered/fracture aquifer)–quartz schist 3.55 (weathered aquifer) with an average of 2.35 indicating moderate groundwater potential. The low, moderate, and high zones constituted 25%, 55%, and 20% respectively of the study area. The high potential zone is prominent in the mid-central and north central parts. Conclusively, the quartz schist and quartzite areas showed better prolificacy than metadioritic environment. But in terms of protective capacity of the aquifers, the longitudinal unit conductance recorded weak regional average of 0.19396 mhos, with quartzite (0.33444 mhos) and quartz schist (0.15218 mhos); and metadiorite recorded 0.1208 mhos, hence metadiorite being the most vulnerable environment. The water table aquifer and the fracture basement are the major water bearing units in the area. The drainage basin falls within the low–moderate regional drainage basins, with moderate to high flow connectivity and low–moderate flow direction. Thus, there’s possibility of movement of water towards the northern part (discharged zone) with the southern area forming the watershed.